Comparison between gait characteristics in a free-living situation and in-laboratory walking among Japanese university students - Tada, Yuki; Sato, Hina; Ishikawa-Takata, Kazuko; Hida, Azumi (Research in Exercise Epidemiology, 2024)
Objective: To evaluate free-living gait characteristics in comparison with in-laboratory walking among Japanese university students.Methods: Gait characteristics (walking speed, step length, and cadence) were measured in a laboratory setting and a free-living situation. In both settings, the gait characteristics were assessed using motion sensors attached to both ankles. In the laboratory setting, subjects walked on a circular course for 5 minutes while maintaining their natural walking speed, which was assessed in 5-m walking tests. In a free-living situation, subjects were asked to wear the devices for 1 week. Frequencies of values higher than, the same as, and lower than the data measured in the laboratory were calculated for the free-living data. The effect of footwear type was also examined in a free-living situation.Results: Eight healthy university students (age: 22.1 ± 0.4 years, six female subjects) completed the study. During the free-living period, the frequencies of slower walking speed, shorter step length, and slower cadence compared with the in-laboratory period were 79.4 ± 14.6%, 69.8 ± 25.3%, and 73.4 ± 15.6%, respectively. Walking speed, step length, and cadence were significantly lower when subjects wore slippers compared with other footwears.Conclusion: Healthy Japanese university students' walking speed, step length, and cadence during free-living were lower compared with the in-laboratory setting. This suggests that the evaluation of walking in an in-laboratory setting may not reflect free-living walking among university students.